Dominant Features of the Yunnan Painting School in the Work of Deng Anke (邓安克) and His Students of the Younger Generation - Zhang, Heng (HUDPROM: The Ukrainian Art and Design Journal, 2024)
In Chinese painting, the study of regional art schools is a crucial area of research. Contemporary Chinese painting is shaped by a variety of local trends, yet European scholars focus on mainstream artistic phenomena. In contrast, the Yunnan painting school holds an extremely strong position, exerting a significant influence on the broader landscape of modern Chinese fine art through its diverse representatives. The aim of the article is to examine the dominant features of the Yunnan painting school through the work of one of the founders of the school, Deng Anke, and his students from the younger generation, Zhou Changxin and Gao Tan. The research methodology is based on historical and genetic analysis, which is essential for understanding the evolution of Yunnan painting across generations. Additionally, the study employs figurative-stylistic analysis as a key method for evaluating artistic tendencies. Deng Anke’s work underscores the importance of regional artistic contexts in contemporary Chinese painting. The unique development of the Yunnan painting school highlights its diverse directions, forming an integral part of the broader repertoire of Chinese oil painting. His works emphasize Yunnan “strong” color painting as a central artistic tradition with a distinct representative significance. The artistic development of Deng Anke’s students, Zhou Changxin and Gao Tan, reflects the ongoing evolution of this regional school. The concept of strong color painting remains dominant in educational practices and continues to shape the work of emerging artists. The study reveals that both Zhou Changxin and Gao Tan actively engage with contemporary trends in Chinese fine art. Zhou Changxin integrates post-traditional aesthetics, incorporating gohua techniques into oil painting, while Gao Tan explores an intergenre space, experimenting with landscape, still life, and narrative painting. Their work, marked by symbolism and broader formal-figurative artistic inquiries, departs from the ethnographic orientation of their teacher, emphasizing the modern trajectory of the Yunnan school.